Effects of K2O Evaporation on the Structural Properties of KSbO3 Compounds. Issue 7 (26th May 2016) - Park, Jongseong; Kim, Dae‐Hyeon; Park, Su‐Jin; Lee, Tae‐gon; Im, Mir; Kim, Jeong‐Seog; Nahm, Sahn
Abstract : A specimen having a stoichiometric composition of KSbO3 ·(KSb) calcined at 800°C has an R 3 ¯ rhombohedral structure (RS), and changes to a Pn 3 ¯ cubic structure (CS) when calcined at 1100°C. Finally, a <111>‐oriented rhombohedral phase is formed in the specimen calcined at 1230°C. K/Sb ratio decreases from 1.0 in RS, 0.93 in CS, and finally to 0.85 in <111>‐oriented rhombohedral phases. On the other hand, a specimen having a K‐excess composition of K1.1 SbO3 calcined at 800°C shows a RS that is maintained in the K‐excess specimen calcined at 1230°C. The composition of these specimens is very close to KSb. Therefore, the RS with a space group of R 3 ¯ is a stable form of KSbO3 . The formation of Pn 3 ¯ cubic and <111>‐oriented R 3 ¯ phases can be explained by the evaporation of K2 O during the calcination process at temperatures above 1100°C.